Chemical-nutritive characterization of plant species consumed by the Amazonian tapir (Tapirus terrestris) - Naranjo, Blanca (2014)
Amazonian tapir (Tapirus terrestris), is an herbivore native of great size and nutritional importance. The efforts by their preservation and study are important, so was remained across II Congreso Ecuatoriano de Mastozoología y I Congreso Latinoamericano de Tapires, recognizing efforts developed through Ecuadorian Amazonia, like this. A Chemical-nutritional characterization of seven vegetal species consumed by T. terrestris, was performed through a proximal analysis (humidity, fat, crude fiber, ash, total protein) by means of conventional techniques. It was determined the true and digestible protein, sugar identification, free amino acids quantification and title able acidity. It was also determined minerals by using atomic absorption, and hidrosolubles vitamins by High Pressure Liquid Chromatography (HPLC). Significant amounts of essential amino acids; a diversity of minerals, in diverse amount; C vitamin, riboflavin and nicotinamin traces were also found. Based on the obtained results the culture and handling of these vegetal species it is recommended as an animal supply resource, also considering that in Amazon it must to know diversity about food fonts that feed both science and it relationship with communities.